1991
DOI: 10.1093/nar/19.2.209
|View full text |Cite
|
Sign up to set email alerts
|

SRP-RNA sequence alignment and secondary structure

Abstract: The secondary structures of the RNAs from the signal recognition particle, termed SRP-RNA, were derived buy comparative analyses of an alignment of 39 sequences. The models are minimal in that only base pairs are included for which there is comparative evidence. The structures represent refinements of earlier versions and include a new short helix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
198
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(205 citation statements)
references
References 43 publications
7
198
0
Order By: Relevance
“…SRP RNA: SRP RNA has a long, double helical structure with one pseudoknot structure close to the 5' end [30], which can be viewed as 'kissing hairpins'. Our structure prediction is based on the alignment of 8 archaeal sequences.…”
Section: Resultsmentioning
confidence: 99%
“…SRP RNA: SRP RNA has a long, double helical structure with one pseudoknot structure close to the 5' end [30], which can be viewed as 'kissing hairpins'. Our structure prediction is based on the alignment of 8 archaeal sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The signal recognition particle (SRP) functions in cotranslational targeting of ribosomes synthesizing proteins with an N-terminal targeting signal to the membrane of the endoplasmic reticulum (ER) in eukaryotes and to the plasma membrane in prokaryotes (Walter & Johnson, 1994;Rapoport et al+, 1996;de Gier et al+, 1997)+ SRP recognizes an N-terminal targeting peptide emerging from the translating ribosomes, and, subsequently, the ribosome-SRP complex binds to the SRP receptor at the membrane+ Compared to mammalian SRP (Walter & Blobel, 1983), bacterial SRP is of simpler composition and consists of one RNA (4+5S RNA) and one protein (Ffh), which share homologies with their respective eukaryotic functional counterparts, 7S RNA (Poritz et al+, 1988) and SRP54 protein (Bernstein et al+, 1989;Römisch et al+, 1989)+ The majority of proteins secreted from bacteria appears to be exported posttranslationally by the SecB pathway, and the SRP pathway may be used for a few proteins only+ However, the SRP pathway in Escherichia coli is essential for membrane insertion of several inner membrane proteins (Ulbrandt et al+, 1997;Beck et al+, 2000), and the SRP and SecB pathways use the same translocon for protein translocation (de Gier et al+, 1998;Valent et al+, 1998)+ Ffh and the bacterial SRP receptor, FtsY, belong to the group of SRP-related GTPases+ Their G domains contain an insertion, I box, in the effector loop, and an N-terminal four-helix N domain that is closely packed against the G domain (Freymann et al+, 1997;Montoya et al+, 1997)+ The M domain of Ffh contains the binding sites for the signal sequence and the SRP RNA (Keenan et al+, 1998)+ The structure of the M domain of human SRP54 is similar (Clemons et al+, 1999)+ SRP and FtsY were reported to moderately stimulate each other's GTPase activity (Powers & Walter, 1995), and a conformational change in the I box region of FtsY upon binding to SRP was demonstrated by fluorescence measurements (Jagath et al+, 2000)+ Eukaryotic SRP RNA (7S RNA) can be divided into four structural domains (I-IV) (Poritz et al+, 1988) or eight helices (Larsen & Zwieb, 1991), of which the most conserved domain IV (or helix 8) is present in all SRP RNAs, including 4+5S RNA from E. coli. The structure of an RNA fragment comprising domain IV of E. coli 4+5S RNA has been determined by NMR (Schmitz et al+, 1999a(Schmitz et al+, , 1999b)+ Genetic and bioch...…”
Section: Introductionmentioning
confidence: 97%
“…The search motifs can be downloaded from our ftp server (see below), so that others may search new data or modify the motifs. The new SRP RNAs were aligned using the rules previously described (6).…”
Section: Descriptionmentioning
confidence: 99%